Risk of Dementia Associated with Elevated Plasma Homocysteine in a Latin American Population. (3rd August 2009) - Chacón, Inara J.; Molero, Aldrín E.; Pino-Ramírez, Gloria; Luchsinger, José A.; Lee, Joseph H.; Maestre, Gladys E.
Abstract : The relationship between total homocysteine (tHcy) and dementia risk remains controversial, as the association varies among populations and dementia subtypes. We studied a Venezuelan population that has high prevalence of both elevated tHcy and dementia. We tested the hypotheses that (1) elevated tHcy is associated with increased dementia risk, (2) the risk is greater for vascular dementia (VaD) than for Alzheimer's disease (AD), and (3) a history of stroke may partly explain this association. 2100 participants (≥55 years old) of the Maracaibo Aging Study underwent standardized neurological, neuropsychiatric, and cardiovascular assessments. Elevated tHcy was significantly associated with dementia, primarily VaD. When history of stroke and other confounding factors were taken into account, elevated tHcy remained a significant risk factor in older (>66 years), but not in younger (55–66 years) subjects. Ongoing studies of this population may provide insight into the mechanism by which tHcy increases risk for dementia.